The genetics and molecular biology of neural tumors - Sandberg, Avery A. (Springer, 2017)
Collecting an extensive amount of information from thousands of publications by leading investigators in this rapidly developing field, The Genetics and Molecular Biology of Neural Tumors provides a convenient and up-to-date one volume source for research in neural tumors of various cellular origins. Each chapter, with a comprehensive list of references and many informative tables, contains clinical and epidemiologic information, as well as succinct but relevant patho-histologic and immunohistochemical descriptions facilitating the interpretation of the findings on tumor genetics and molecular biology. With over 3,500 references, 110 figures and 120 tables, this volume gathers an astonishing body of knowledge regarding human neural tumors. As a ready and concentrated source, The Genetics and Molecular Biology of Neural Tumors is the perfect reference for busy clinicians, clinical investigators and laboratory researchers struggling through the copious and far-spread research on this subject